PEMANFAATAN CITRA SATELIT DAN SISTEM INFORMASI GEOGRAFIS UNTUK PEMETAAN KESESUAIAN AGROKLIMAT TANAMAN JAGUNG DI PROVINSI JAWA TENGAH - Apritarum Fadianika; I Wayan Nuarsa; I Ketut Sardiana (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2023)
Corn is a strategic agricultural commodity in Central Java Province because this plant is the second main food crop commodity after rice. Evaluation of agro-climate suitability aims to assess suitable areas based on climatic conditions and efforts to overcome climate-limiting factors in order to achieve optimal productivity in corn cultivation. Satellite imagery can be used to overcome the lack of density of climate stations, which are the source of data for climate suitability evaluation. This study aims to validate GSMaP satellite rainfall data and Terra MODIS satellite air temperature data against BMKG observation data, create a distribution map of climatic conditions, and create a distribution map of agro-climate suitability classes based on GIS for maize in Central Java Province. This study uses rainfall and temperature data from 30 BMKG observation points and satellite imagery data for 20 years (2001–2020). The correlation values, RMSE, and MBE were calculated to validate satellite rainfall and air temperature data with observed rainfall and air temperature. Satellite data correction calculations are used to fill in the data at points without observation. The validation results show that the satellite data is valid and that there is a pattern of conformity with the observational data. Central Java province has an annual rainfall of 1,500 mm/year to 6,000 mm/year, an average annual temperature of 24.9oC to 28.1oC, and three to nine months of wet months. In some areas, the agro-climate suitability class for maize plants was in the moderately suitable category (S2wa, tc) with an area of 156,302 ha, marginally suitable (S3wa) with an area of 1,277,813 ha, and not suitable (Nwa) with an area of 2,008,673 ha. Keywords: Corn; GSMaP; Terra MODIS; Climate Suitability; GIS